2005
DOI: 10.1590/s1516-35982005000300025
|View full text |Cite
|
Sign up to set email alerts
|

Características da carcaça de vacas de descarte de diferentes grupos genéticos terminadas em confinamento com distintos pesos

Abstract: RESUMO -Foram avaliadas as características da carcaça de vacas de descarte mestiças e da segunda (G2 -3/4Charolês (C) 1/4Nelore (N) e 3/4NC) e terceira gerações (G3 -5/8CN e 5/8NC) do cruzamento rotativo Charolês -Nelore, terminadas em confinamento e abatidas com 465, 507 ou 566 kg. Os animais apresentaram, no início do confinamento, em média, 8,5 anos de idade, 388,6 kg e 2,35 pontos de escore de condição corporal. A dieta, com relação volumoso:concentrado de 48:52, continha 12,5% de proteína bruta e 2,99 Mca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
18
2
29

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 19 publications
10
18
2
29
Order By: Relevance
“…Backfat thickness (BFT) and fat cover degree increased linearly along with the body weight of animals (Table 6), which is in line with the reports found in the literature (Galvão et al, 1991;Restle et al, 1997;Leme et al, 2000;Kuss et al, 2005), wherein we observe an increase of 0.028 mm BFT for each increase in body weight. The fat cover in the carcass is important, because it reduces the losses by dehydration during cooling.…”
Section: Resultssupporting
confidence: 92%
“…Backfat thickness (BFT) and fat cover degree increased linearly along with the body weight of animals (Table 6), which is in line with the reports found in the literature (Galvão et al, 1991;Restle et al, 1997;Leme et al, 2000;Kuss et al, 2005), wherein we observe an increase of 0.028 mm BFT for each increase in body weight. The fat cover in the carcass is important, because it reduces the losses by dehydration during cooling.…”
Section: Resultssupporting
confidence: 92%
“…In the present study, total average bone yield was 17.65% (Table 8), not taking into consideration rib bones, as the rib cuts were prepared with bone in. Summing the 1.96% rib bone yield obtained by (Osório et al, 1995;Junqueira et al, 1998;Ledic et al, 2000;Coutinho Filho et al, 2006;Bonilha et al, 2007;Tarouco et al, 2007) found lower percentages of edible cuts, and higher percentages of bone than those that reported the method proposed by Hankins & Howe (1946) (Perotto et al, 2000;Feijó et al, 2001;Vaz & Restle, 2005;Kuss et al, 2005;Canesin et al, 2006). The studies using the direct assessment method for deboning obtained 19.08% average bone yield, whereas those applying the HH method achieved 16.85%, resulting in a 3.23% difference.…”
Section: Resultsmentioning
confidence: 80%
“…Generally, the similarity amongst treatments for the variables related to the carcass traits can be attributed to the similar weight conditions under which they were slaughtered (Kuss et al, 2005). In studies on finishing steers (Mach et al, 2009;Bartoň et al, 2013) and calves (Ramos and Kerley, 2012), similar carcass traits were described when compared with animals fed a diet without crude glycerin and diets with up to 200 g kg −1 crude glycerin.…”
Section: Discussionmentioning
confidence: 99%